Estudio de correlación genética de producción de leche y características corporales en toros GYR comercializados por catálogo en ecuador durante 2017- 2020 - Alcívar Ronquillo, Edisson Andrés (2022)
The objective of this study was to estimate the genetic correlation between Predicted Transmission Ability (HTP) of production, milk quality parameters and body characteristics in Gyr bulls with genetic evaluation available in Ecuador. The data was obtained through the database of the commercial houses that sell these bulls in Ecuador, 23 of them that met the HTP parameters were taken. These parameters were analyzed by means of descriptive statistics where a linear correlation analysis was carried out by the Pearson method, using the software for statistical analysis Infostat 2019. The results of the genetic correlations between production and body characteristics show that a large part of they give negative values and of low significance, where the most relevant in terms of milk production with linear characteristics occurred in milk fat yield and leg position (curvature-side view) with a value of 0.562 , while related to the characteristics of the udder, it was presented in the correlation of milk production with depth of the udder with a value of 0.693; likewise, the relationships between body characteristics are given in length of the rump with width between the ilium with a value of 0.748, and related to those of the udder, it shows a correlation between the rear udder and the position of the leg (curvature - side view) with a value of 0.622. It is concluded that not all the characteristics of the marketed bulls have significant correlations.